Genetic Mouse Models of Alzheimer's Disease - Yann S. Mineur; Declan McLoughlin; Wim E. Crusio; Frans Sluyter (Neural Plasticity)
In the current minireview, we focus on genetic mouse models of Alzheimer's disease (AD). Because various excellent, up-to-date reviews, special issues, and reliable websites are already dedicated to the genetics of Alzheimer's disease in general and of animal models in particular, this review is not meant to be comprehensive. Rather, we aim to steer the Alzheimer's novice through the recent mouse literature on AD. Special attention will be paid to genetic models that have been tested behaviorally.